Enhanced activation of peroxymonosulfate by nitrogen doped porous carbon for effective removal of organic pollutants. (May 2017) - Wang, Guanlong; Chen, Shuo; Quan, Xie; Yu, Hongtao; Zhang, Yaobin
Abstract: Nitrogen doped nanocarbon materials have emerged as promising metal-free catalysts towards peroxymonosulfate (PMS) activation for environmental remediation. However, their catalytic efficiency for PMS activation still needs improvement. Moreover, the relationship between the catalytic efficiency and nitrogen content or species, which is important to clarify the catalytic mechanism, remains unclear. In this study, three nitrogen-rich metal-organic frameworks (ZIF-8, NH2 -MIL-53 and IRMOF-3) with nitrogen content of 24.7 wt%, 6.28 wt% and 5.16 wt% respectively were chosen to prepare the nitrogen doped porous carbons (NPCs) with different nitrogen content. Several carbonization temperatures were employed to obtain the NPCs with varying nitrogen species. The PMS catalytic performance of NPCs and its relationship with nitrogen content or species were investigated. The results showed all the NPCs exhibited enhanced PMS activation for phenol degradation compared with the nitrogen-free porous carbon (obtained from MOF-5), and was even superior to the most effective PMS activator of homogeneous Co 2+ . The ZIF-8 derived NPC carbonized at 1000 °C, with the highest graphitic N content, displayed best performance with the kinetic constant of phenol degradation 4 times higher than that on porous carbon. The graphitic N plays a critical role for activating PMS to produce sulfate radical and hydroxyl radical. Graphical abstract: